Os discursos sobre criptomoedas e blockchain na produção acadêmica brasileira: uma crítica à neutralidade da técnica e ao determinismo tecnológico - Mello, Rael Dill de (2022)
Technological development is often associated with social development. The enthusiasm for new technologies and the belief that they transform social relations in an evolutionary and accumulative way come to assume a mythical character, attributing to technology an almost magical ability to change the human world. Through technological determinism and the neutrality of technique, technology is stripped of its social determinations to be understood in a unilateral relationship with society. With the emergence of bitcoin, cryptocurrencies, blockchain and related technologies have become a symbol of a new step in technological development towards a freer and more democratic world. As they are relevant innovations of today, they represent the image of a neutral, rational and objective solution to problems of a political and economic nature. Aiming to identify and discuss the technological determinism and the neutrality of the technique in the discourses, this research carried out an analysis of the final papers of Brazilian graduate students whose main object was bitcoin, blockchain and cryptocurrencies. For this, the research used the field of studies in Science, Technology and Society (CTS) and historical-dialectical materialism. After a brief characterization of the productions, it was found that the fetishized view of technology is hegemonic in the productions. The discussion was divided into four moments. The first on technological development as an efficiency in the society of value appreciation. In the second, it focused on how technology dresses itself in neutrality to modify (or reproduce) power relations in today’s society. The third focused on individualism and its expressions in speeches, especially those dealing with cryptocurrencies. Finally, to discuss the generic and abstract character that the ideas of State and territory assume in the productions. It is concluded that the perspective adopted on technology, for the most part, disregards technological development as the development of productive forces because it abstracts the peculiar production relationship of capitalism, where technical inventions are applied aiming at the highest rate of extraction of more value, and not the emancipation of exploited labor and an increase in free time. We emphasize the need for critical readings on technological development and questions less focused on the specific forms in which technology takes on its path and more focused on power relations and the distribution of private property.